2023
DOI: 10.3390/nu15030486
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and Asthma: Microbial Dysbiosis and the Origins, Phenotypes, Persistence, and Severity of Asthma

Abstract: The importance of the microbiome, and of the gut-lung axis in the origin and persistence of asthma, is an ongoing field of investigation. The process of microbial colonisation in the first three years of life is fundamental for health, with the first hundred days of life being critical. Different factors are associated with early microbial dysbiosis, such as caesarean delivery, artificial lactation and antibiotic therapy, among others. Longitudinal cohort studies on gut and airway microbiome in children have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 148 publications
0
22
0
Order By: Relevance
“…Exogenous factors influence the pathogenesis of asthma by affecting the microbiome. Gut microbial dysbiosis leads to low alpha diversity of gut bacteria and reduced the abundance of phylum Firmicutes, which increases the risk of asthma 42 . Studies have shown that Proteobacteria are abundant in the respiratory tract of asthmatic patients 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous factors influence the pathogenesis of asthma by affecting the microbiome. Gut microbial dysbiosis leads to low alpha diversity of gut bacteria and reduced the abundance of phylum Firmicutes, which increases the risk of asthma 42 . Studies have shown that Proteobacteria are abundant in the respiratory tract of asthmatic patients 43 .…”
Section: Discussionmentioning
confidence: 99%
“…41 Firmicutes, which increases the risk of asthma. 42 Studies have shown that Proteobacteria are abundant in the respiratory tract of asthmatic patients. 43 In the airway microbiota of asthmatic patients, the most dominant bacteria at the phylum level are Firmicutes, followed by Proteobacteria and Actinobacteriota.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to variations in sampling locations, techniques, and time points, generalizing outcomes from these studies has proven challenging. 58,59 Akin the studies of the gut microbiome, there are six studies of the upper airways with a longitudinal design that evaluate the microbiome in infants (0-2 years) and correlate this with an asthma diagnosis later in infancy (2-18 years) 39,40,[60][61][62][63] (Table 2). Three of the six studies in the airways, reported diversity.…”
Section: Airway MI Crob I Ome and A S Thmamentioning
confidence: 99%
“…A study looking at participants with asthma alone, allergic rhinitis alone, asthma with allergic rhinitis, and healthy controls found significant differences in the dominant, alpha-diversity indices of microbial richness and beta-diversity indices when comparing the groups [23]. Additionally, a lower abundance of gut Firmicutes and an upper airway presence of Moraxella species have both been associated with an increased risk of development of asthma [24]. Given the relationship between allergic disease and the microbiome in other organ systems, it would follow that there is also a connection between allergic eye diseases and the ocular surface microbiome.…”
Section: Systemic Allergic Disease and Its Relationship To Extraocula...mentioning
confidence: 99%